2018
DOI: 10.4103/ua.ua_136_17
|View full text |Cite
|
Sign up to set email alerts
|

Primary urethral carcinoma: A Surveillance, Epidemiology, and End Results data analysis identifying predictors of cancer-specific survival

Abstract: Objectives:Primary urethral carcinoma (PUC) is rare, accounting for <1% of genitourinary malignancies. Current knowledge regarding is founded upon tertiary care centers reporting their experiences. We aim to identify factors predictive of outcomes using a nationwide registry database.Materials and Methods:The Surveillance, Epidemiology, and End Results-18 registries database was queried for cases of PUC ranging between 2004 and 2010. To identify PUC cases, ICD-O site code C68.0 was used as a filter, hence iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…The most frequent sites of occurrence are the urethra bulb and membranous urethra followed by the pendulum part and prostatic urethra. Histologically, UC, AC, and SCC account for 24.9%, 46.7%, and 25.4% of urethral malignancies in female patients and 53.6%, 11.6%, and 34.8% of urethral malignancies in male patients, respectively . Clear cell carcinoma is categorized as an AC with columnar and mucinous cell carcinoma types …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent sites of occurrence are the urethra bulb and membranous urethra followed by the pendulum part and prostatic urethra. Histologically, UC, AC, and SCC account for 24.9%, 46.7%, and 25.4% of urethral malignancies in female patients and 53.6%, 11.6%, and 34.8% of urethral malignancies in male patients, respectively . Clear cell carcinoma is categorized as an AC with columnar and mucinous cell carcinoma types …”
Section: Discussionmentioning
confidence: 99%
“…Histologically, UC, AC, and SCC account for 24.9%, 46.7%, and 25.4% of urethral malignancies in female patients and 53.6%, 11.6%, and 34.8% of urethral malignancies in male patients, respectively. 3 Clear cell carcinoma is categorized as an AC with columnar and mucinous cell carcinoma types. 1,2 CCA is frequently seen in women, and some cases have been reported as diverticulum tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, UC, AC, and SCC account for 24.9%, 46.7%, and 25.4% of urethral malignancies in female patients and 53.6%, 11.6%, and 34.8% of urethral malignancies in male patients, respectively. 1 Although there are no typical symptoms of urethral cancer, and previously reported cases have shown that dysuria and hemorrhage occur in some patients. 2 These symptoms are often seen in healthy adult women, and due to the low incidence of female urethral carcinoma, it is usually difficult to diagnose based on the symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Urethral cancer accounts for 0.02% of all malignant diseases in female patients. Histologically, UC, AC, and SCC account for 24.9%, 46.7%, and 25.4% of urethral malignancies in female patients and 53.6%, 11.6%, and 34.8% of urethral malignancies in male patients, respectively . Although there are no typical symptoms of urethral cancer, and previously reported cases have shown that dysuria and hemorrhage occur in some patients .…”
Section: Introductionmentioning
confidence: 99%
“…Primary PUC is a rare genitourinary malignancy arising from the epithelial lining of the urethra [1] and should be differentiated from urothelial cancer arising from the bladder as well as squamous carcinoma arising from the penile glans [2]. Urethral cancer histologically can be adenocarcinoma, squamous, or urothelial, and a retrospective study showed that many of these cancers can have squamous and urothelial histologic features [2].…”
Section: Introductionmentioning
confidence: 99%